2019
DOI: 10.3390/su11226432
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Capital Increase Innovation Speed? Empirical Evidence from China

Abstract: Past studies have suggested that social capital is a sustainable competitive advantage that leads to sustainable organizational growth and performance. However, few studies have explored how innovation speed moderates the relationship between social capital and sustainable organizational performance in China where the government plays key roles in promoting sustainable development goals. This paper develops a “social capital-innovation speed-performance” framework to investigate the mechanism of social capital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 84 publications
1
39
0
Order By: Relevance
“…As some research has shown (Langerak and Hultink, 2006;Shan et al, 2016;Zhang et al, 2019), there are both benefits and costs of accelerating innovation speed (Kessler and Bierly, 2002;Zhang et al, 2019). Firms that are the fastest innovators have first-mover benefits that far outweigh the costs of high innovation speeds, which in turn leads to high performance, providing support for the prior studies (Shan et al, 2016;Zhang et al, 2019). But the slowest innovators can reap follower benefits and do not bear the cost of rapid innovation, which also leads to higher performance outcomes.…”
Section: Cross National Similarities and Differencesmentioning
confidence: 82%
See 4 more Smart Citations
“…As some research has shown (Langerak and Hultink, 2006;Shan et al, 2016;Zhang et al, 2019), there are both benefits and costs of accelerating innovation speed (Kessler and Bierly, 2002;Zhang et al, 2019). Firms that are the fastest innovators have first-mover benefits that far outweigh the costs of high innovation speeds, which in turn leads to high performance, providing support for the prior studies (Shan et al, 2016;Zhang et al, 2019). But the slowest innovators can reap follower benefits and do not bear the cost of rapid innovation, which also leads to higher performance outcomes.…”
Section: Cross National Similarities and Differencesmentioning
confidence: 82%
“…For example, Chen et al (2012) found that accelerating the pace of innovation can continuously improve the novelty of products, meet the changing needs of consumers more quickly, improve consumer perception, and gain more consumer favor and loyalty. Zhang et al (2019) indicated that faster innovation speed leads to stronger core capabilities, more opportunities, and better consumer satisfaction. Some research has suggested that rapid innovation also increases the likelihood of establishing industry standards, building brand image, and enhancing the firms' profile and reputation (Song et al, 1999;Lee et al, 2000;Langerak and Hultink, 2006).…”
Section: Innovation Speed and Performancementioning
confidence: 99%
See 3 more Smart Citations